Personal identity during the Time of Troubles in Russia (setting up a problem) - A.A. Kuznetsov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper considers the phenomenon of personal identity development and democratization of the history of Russia during the Time of Troubles. D.S. Likhachev’s opinion on the discovery of a personality in the Russian literature of the 17th century is discussed. It is demonstrated that the problem of personal identity in the socio-political space of Russia was raised for the first time during the Time of Troubles. Hunger, devastation, deprivation, underestimation of the value of human life paradoxically promoted the development of a view on the personal identity as an important element of life. The historical and anthropological problem of studying the formation and development of self-identification in Russia under the influence of destructive and tragic events of the Time of Troubles is formulated. The above problem can be solved by carrying out a mass biographical research based on numerous sources and using the methods of prosopography and historical anthropology. The unremitting wars that took place in the second half of the 16th century favored the development of personal identity at the public level. A generation of nobles accustomed to making decisions under the war conditions emerged. In the Time of Troubles, other social groups adopted the behavioral strategies of the nobility. As a result, imposture, unregulated (both traditionally and legally) leadership in the Cossack hosts, robber gangs, and self-organized grouping became common. Under these circumstances, people were willing to actively participate in the events of the Time of Troubles and in the changes of the political course. Therefore, the historical sources confirm that the history of Russia exhibited the first sings of democratization during the Time of Troubles.